Analysis of Ceramic Compositional Data from Late Developmental Period Sites in the Tewa Basin, New Mexico. Issue 1 (2nd January 2020) - Schillaci, Michael A.; Lakatos, Steven A.; Ferguson, Jeffrey R.; Wilson, C. Dean
Abstract : The presence of Cibola white ware ceramic types at Late Developmental period sites in the Northern Rio Grande (NRG) region of New Mexico has been interpreted as a strong indicator of cultural interaction with, or immigration from, communities associated with the Chaco regional system in the American Southwest. We report the results of an analysis of chemical composition data obtained from neutron activation analysis (NAA) of pottery sherds originating from three Late Developmental sites in the southern Tewa Basin of the NRG. Our results revealed three compositional groups, one local and two non-local. Comparison with existing data sets allowed us to identify specific production areas and great house communities within the Chaco regional system as likely sources for one of the two non-local groups. Our findings also revealed five sherds of a local NRG pottery type, Kwahe'e B/w that were made with non-local clay from the Chaco regional system, but were tempered with local materials.